Major and trace element concentrations in sediments of ODP Hole 184-1144A in the South China Sea (Appendix A) - Gangjian Wei; Ying Liu; Xian-hua Li; Lei Shao; Dianyong Fang (PANGAEA, 2004)
We present here the major and trace element data of the sediments at ODP Site 1144 of the last 230 ka with time resolution about 1.5 kyr to investigate their relations to the climate changes. Estimated from TiO2 and CaO contents, over 70% in weight of the sediments are terrestrial materials, and CaCO3 abundance ranges between 7% and 19%. The variation patterns of some of the major elements, such as Al, Fe, K, Mg and Mn, and some of the trace elements, such as the alkali elements (such as Rb and Cs), the alkali earth elements (such as Ba) and most transition metals (such as Sc, V, Co, Cr, Zn), well match that of the oxygen isotopes of the planktonic foraminifer, after normalized with Ti, with higher values during interglacial periods and lower values during glacial periods. Whilst the Na abundance exhibits inverse variation patterns with lower values during interglacial periods and higher values during glacial periods. However, most refractory elements, such as Y, Zr, Nb, Hf, Ta, REEs, Th and U, do not show such patterns. These agree well with the behaviors of these elements during chemical weathering. Therefore, the changes of chemical weathering intensity in South China, the source area of these sediments may account for such variation patterns. During interglacials, wet and warm climate might occur at South China, which resulted in stronger chemical weathering, and dry climate might occur during glacials, which resulted in weaker chemical weathering. Such paleoclimate interpretation agrees with those from other paleoclimate proxies, such as pollen records, indicating that change of the East Asian monsoon, especially change of the winter monsoon is the key for such paleoclimate variation patterns.
Supplement to: Wei, G et al. (2004): Major and trace element variations of the sediments at ODP Site 1144, South China Sea, during the last 230 ka and their paleoclimate implications. Palaeogeography, Palaeoclimatology, Palaeoecology, 212(3-4), 331-342, https://doi.org/10.1016/j.palaeo.2004.06.011